Structure and superfluidity of 4He films on plated graphite - Nyeki, J.; Ray, R.; Sheshin, G.; Maidanov, V.; Mikheev, V.; Cowan, B.; Saunders, J. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 1997)
The results of an experimental study using torsional oscillators of the superfluidity of 4He films adsorbed on hydrogen plated graphite are reported. The evolution of superfluidity with the growth of the film shows considerable structure arising from the atomic layering of the film. There is evidence that the superfluidity of a single fluid layer is strongly suppressed, possibly due to the influence of the periodic potential arising from the underlying solid layer. The behavior of two fluid layers is quite distinct, but shows similarities to that of thicker films on heterogeneous substrates; we suggest that the usual theory of the superfluidity of two-dimensional 4He should be extended to account for superfluid 2onset temperatures in such a film.